Utilization of the ELECTRE and SMART Algorithms for Determining the Head of Administration for the Gunung Maligas Sub-District Office - Fajar Ramadan; Rahmat W. Sembiring; Anjar Wanto (Yayasan Literasi Sains Indonesia, 2023)
This study aims to apply the ELECTRE (Elimination and Choice Expressing Reality) and SMART (Simple Multi-Attribute Rating Technique) algorithms in determining the administrative head of the Gunung Maligas sub-district office. The head of administration is an important position in a government organization responsible for managing various administrative and coordinating activities. The ELECTRE method produces an alternative ranking of administrative head candidates based on multiple relevant attributes. Work experience, communication skills, organizational knowledge, and leadership skills are considered. The SMART method assigns weights to each point and combines attribute values to produce an overall score for each candidate. The data in this study were obtained through surveys and interviews with related parties. After the data is collected, an analysis process is carried out using the ELECTRE and SMART algorithms to produce a ranking of candidates that best suit the needs of the Gunung Maligas sub-district office. The results of this study are expected to provide objective and accurate recommendations for selecting qualified administrative heads. By using the ELECTRE and SMART algorithm approaches, the process of determining the executive authority can be more efficient and effective and help improve managerial performance and coordination at the Gunung Maligas sub-district office.